2022
DOI: 10.1177/00224669221090231
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Synthesis of Disability Research in Western Africa

Abstract: Most disability research is conducted in high-income countries, despite much of the world’s population living in low- and middle-income countries. Given the flexible nature of qualitative research, studies using this methodology have the potential to provide important insights into how disability is perceived across the globe. The aim of the current study was to synthesize the results of disability research in Western Africa to elucidate prominent themes and identify methodological and participant characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Sierra Leone, in particular, has a paucity of disability research. According to a recent large-scale meta-synthesis of qualitative disability research in West Africa, a mere 11 studies had been conducted in Sierra Leone compared to 212 studies conducted in other West African countries (Blasko et al, in review). What little information is known about disabilities in Sierra Leone often comes from national census data, which are self-report measures, and focuses on quantitative measures of disability, such as frequency, employment rate, and educational attainment (Kabia & Tarawally, 2017).…”
mentioning
confidence: 99%
“…Sierra Leone, in particular, has a paucity of disability research. According to a recent large-scale meta-synthesis of qualitative disability research in West Africa, a mere 11 studies had been conducted in Sierra Leone compared to 212 studies conducted in other West African countries (Blasko et al, in review). What little information is known about disabilities in Sierra Leone often comes from national census data, which are self-report measures, and focuses on quantitative measures of disability, such as frequency, employment rate, and educational attainment (Kabia & Tarawally, 2017).…”
mentioning
confidence: 99%
“…Westernised disability systems and philosophies of disability are likely to be overrepresented in the findings of this review. Blasko et al (2022) identified in their meta‐analysis that research in disability disproportionately concerns high‐income countries, even though most people living with disability globally live in middle‐ and low‐income countries. Jagoe et al (2021) highlight that there are specific barriers to engaging people with disabilities in research in low‐income countries, which prevents the success of global efforts to reduce poverty.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of research on the prevalence of ID in Nigeria (see [6]), it is not possible, other than through extrapolations from other countries, to estimate the overall number of people with ID [4] (p. 88), [6]. In 2018, the World Health Organization estimated that 29 million people in Nigeria were living with a disability [7].…”
Section: Introductionmentioning
confidence: 99%
“…The literature has consistently acknowledged the scarcity of information and empirical research about people with ID in developing countries such as Nigeria, e.g., [2,4,24]. For example, a recent meta-synthesis [6] of disability research in Western Africa revealed that, of the 223 disability articles from West Africa reviewed, only 24 were papers related to people with ID in the whole of West Africa; however, there was no information from the meta-synthesis on how many of these 24 ID studies were specifically derived from Nigeria [6]. To our knowledge, there has been no published scoping review on ID research in Nigeria.…”
Section: Introductionmentioning
confidence: 99%